2021
DOI: 10.1101/2021.07.14.452298
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population model of Temnothorax albipennis as a distributed dynamical system: I. self-consistent threshold is an emergent property in combination of quorum sensing and chemical perception of limited resource

Abstract: House hunting of ant, such as Temnothorax albipennis, has been shown to be a distributed dynamical system. Such a system includes agent-based algorithm [1], with agents in different roles including nest exploration, nest assessment, quorum sensing, and brood item transportation. Such an algorithm, if used properly, can be applied on artificial intelligent system, like robotic swarms. Despite of its complexity, we are focusing on the quorum sensing mechanism, which is also observed in bacteria model. In bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In common with mass recruitment, tandem running in Temnothorax ants may actually involve some trail laying by the leading ant ( Basari et al, 2014b ), but such trails are neither slavishly followed nor reinforced; rather, they may serve as safety lines to help ensure that individuals do not become lost ( Mcleman et al, 2002 ; Pratt et al, 2001 ). Behavioural studies have suggested which pheromone glands are used by Temnothorax ants for communication in different circumstances ( Möglich, 1979 ; Möglich et al, 1974 ; Morgan, 2008 ; Provost et al, 1993 ; Qiu, 2021 preprint; Sasaki et al, 2020 ). However, we agree with Sasaki et al (2014) that little is known of the pheromone chemistry of Temnothorax .…”
Section: Introductionmentioning
confidence: 99%
“…In common with mass recruitment, tandem running in Temnothorax ants may actually involve some trail laying by the leading ant ( Basari et al, 2014b ), but such trails are neither slavishly followed nor reinforced; rather, they may serve as safety lines to help ensure that individuals do not become lost ( Mcleman et al, 2002 ; Pratt et al, 2001 ). Behavioural studies have suggested which pheromone glands are used by Temnothorax ants for communication in different circumstances ( Möglich, 1979 ; Möglich et al, 1974 ; Morgan, 2008 ; Provost et al, 1993 ; Qiu, 2021 preprint; Sasaki et al, 2020 ). However, we agree with Sasaki et al (2014) that little is known of the pheromone chemistry of Temnothorax .…”
Section: Introductionmentioning
confidence: 99%